PRODUCING STUDENT ACHIEVEMENTS AMIDST LIMITED ACCESS TO EDUCATION IN REMOTE AREAS - Safira, Berta; Amaliya, Ana; Dewi, Hermala; Faizah, Siti; Nai’mah, Wardatun; Karamiyah, Wasi’atul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
infrastructure, lack of educational resources, and lack of access to technology. However, students from this region still have the potential to excel if supported by the right approach. Strategies such as strengthening the role of communities, special training for teaching staff, and implementing simple technology can be effective solutions in improving the quality of education. Apart from that, support from the government and private institutions in the form of mentoring programs and the provision of learning facilities also plays a significant role in creating a conducive learning environment. With a holistic and collaborative approach, limited access to education can be overcome, so that producing outstanding students in remote areas becomes a reality that can be realized.